Acompanhamento domiciliar de idoso de unidade da saúde da família de Botucatu - Bôas, Paulo José Fortes Villas [UNESP]; Souza, Milena Luckesi de; Augusto, Mariana Cristina; Floripes, Tricia Maria Feitosa (FapUNIFESP (SciELO), 2012)
Introduction: One of the projects conducted by the Educational Program for Health Work (PET-Saúde) at the Botucatu School of Medicine (Unesp) focuses on comprehensive healthcare for the elderly through homecare. Objective: The objective was to conduct homecare for the elderly through the Family Health Unit, measuring impact and describing the medical students’ perceptions of the care. Methodology: The team consisted of a tutor, three preceptors, and 12 medical students. Each student monitored one elderly patient, applying the Expanded Geriatric Assessment, with an emphasis on functional capacity. Each home visit was followed by discussions and proposals for non-pharmacological treatment plans. Results: Fifteen elderly individuals were assessed, and 12 were monitored, with a mean age of 84.3 years (± 2.6), 75% of whom were women. Sixty-seven percent were dependent in their ADL (activities of daily living) and 85% for IADL (instrumental activities of daily living). None of the elderly individuals required hospitalization during the homecare. Students reported a better understanding of population aging and the appropriateness of homecare for the elderly. Conclusions: The activities allowed establishing a bond among the team and fostered students’ interest in care for the elderly. The methodology facilitated integration between teaching and the health service.

Introdução: Um dos projetos desenvolvidos pelo Programa de Educação pelo Trabalho para a Saúde (PET-Saúde) da Faculdade de Medicina de Botucatu – Unesp é voltado à atenção integral à saúde do idoso: Acompanhamento Domiciliar (ACO). Objetivos: Realizar ACO em idosos de USF, mensurando o impacto de medidas, e descrever a percepção de acadêmicos quanto ao ACO. Metodologia: A equipe era composta por um tutor, três preceptores e 12 acadêmicos. Cada aluno realizou o acompanhamento de um idoso, aplicando a Avaliação Geriátrica Ampla, com ênfase na capacidade funcional. Após cada visita, eram realizadas discussões e propostos planos terapêuticos intervencionais não medicamentosos. Resultados: Avaliaram-se 15 idosos e foram acompanhados 12, com média etária de 84,3 (± 2,6) anos, sendo 75% do sexo feminino. Tinham dependência para AVD (atividades de vida diária) 67% e para AIVD (atividades instrumentais de vida diária) 85%. Durante o ACO, nenhum idoso necessitou de internação. Os acadêmicos relataram melhor compreensão do envelhecimento populacional e a adequação do ACO como forma de atenção à saúde dos idosos. Conclusões: As atividades permitiram o estabelecimento de vínculo entre a equipe. O interesse do acadêmico na atenção à saúde do idoso foi atingido. A metodologia facilitou o processo de integração ensino-serviço.
Homecare monitoring of elderly patients by the family health unit in Botucatu, São Paulo
Keywords: Elderly; Home care monitoring; Geriatrics; Idoso; Assistência domiciliar; Geriatria